Examining the association between lower-limb muscle complaints and muscle function in soccer players - Wakefield, K. J.; Whalan, M. D.; Lovell, R.; Sampson, J. A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Purpose: Lower-limb power, flexibility and hamstring strength are risk factors for time-loss injury; however, Fuller`s 2006 consensus statement highlights injury as any physical complaint. This study therefore examined the hypothesis that muscle complaints will negatively correlate with lower limb flexibility, power and hamstring strength. Methods: 19 semi-professional soccer players (Male, 24 ± 3.1 yrs, 75.5 ± 9.5 Kg, 178.7 ± 6.0 cm) were recruited. Lower-limb power was assessed during 3 counter-movement jumps (Kistler portable force platform, CH-8408 Winterthur, Switzerland). Flexibility assessments of the hamstrings, quadriceps, calves and groin were performed using goniometry. Hamstring strength was assessed via maximum isometric (prone, 30° knee flexion) and isokinetic (prone, 0-135° concentric/eccentric knee flexion 60°/S) dominant limb contractions. Muscle complaints were recorded weekly (frequency), allocated a numerical value from 0-3 (based on reduction of participation) and summed to calculate a severity score (Clarsen et al., 2013). Pearson`s correlations (r2) were performed with significance set at p 0.05. Results: 174 muscle complaints with a severity score of 190 were recorded. Hamstring complaints (47) were negatively associated with quadriceps flexibility (r2=0.34; p=0.0086). Groin complaints (15; r2=0.43; p=0.0023) and their severity (25; r2=0.32; p=0.0114) were negatively correlated with adductor flexibility. No other relationships were observed. Discussion/conclusion: Flexibility measures were most associated to the frequency and severity of muscle complaints. The direct association between groin complaints and poor adductor flexibility is consistent with existing time-loss-groin injury reports (Ekstrand & Gillquist, 1982). Poor quadriceps flexibility has been shown to increase torque on the hamstring muscles during the late swing phase of sprinting, increasing hamstring injury risk (Gabbe et al., 2005). The effect of which could explain the indirect association we observed between hamstring complaints and poor quadriceps flexibility. In contrast to previous work, hamstring muscle strength assessments were not correlated with hamstring complaints. In summary, the results support a groin flexibility screening process to detect and prevent adductor injury.